External Immune Inhibitory Efficiency of External Secretions and Their Metabolic Profiling in Red Palm Weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae) - Pu, Yu-Chen; Xiang, Hai-Jun; Liang, Xin-Yu; Wang, Yu; Hou, You-Ming; Fu, Lang; Wang, Rui (Frontiers in Physiology, 2020)
External secretions play a vital role in external immune defense. However, the functions and components of these exudates are largely unknown in the red palm weevil, Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae). In order to determine their role in external immunity, the immunosuppressive efficacy of the secretions in vitro against microbes, including bacteria and fungi, was clarified. In the present study, we found that these secretions had antimicrobial activity in vitro, implying external immunizing potency against pathogens. Surprisingly, all liquid phases of secretions could not significantly inhibit the growth of microbes in vitro compared to solid phases. To explain this phenomenon, the composition and emission differentia of secretions from the exocrine glands associated with different developmental stages, secretory regions and phases were identified and analyzed based on metabonomics technique. A total of more than two hundred compounds, including quinines, phenols, aldehydes, acids, alcohols, saccharides, ketones, esters, amines, salts, ureas and heterocycles, were identified in the secretions of larvae and adults. The liquid phase shared a number of metabolites with the solid phase, but the emission types and amounts were significantly different in the two phases, resulting in differences in external immunological activity. Tyrosine and p-benzoquinone were the dominant metabolites in all of the secretions, accounting for approximately 11.29% of emissions, with the portion in the solid phase being generally higher than the liquid phase. Moreover, only p-benzoquinone was entirely significantly up-regulated in the solid phase compared to the liquid phase. Therefore, metabolome analysis suggested that p-benzoquinone, which may potentially be developed to be a valuable marker for determining external immunity, was considered to be the main substance responsible for external immune functions. This hypothesis was further demonstrated by the antimicrobial activity of p-benzoquinone.